A formação inicial de professores de ciências no estágio supervisionado : compreendendo a identidade docente a partir da teoria das representações sociais e da epistemologia de Ludwik Fleck - Takahashi, Bruno Tadashi (2018)
In the initial formation of Science teachers we can highlight the investigations that have been focusing on the social factor. In this sense, the teaching identity is a field of research in growth for investigating the construction of the meaning of the profession from the personal experience and its socialization. Thus, the discipline of Supervised Internship for Science Teaching, of the undergraduate courses in Biological Sciences, is configured as a relevant space of investigation of the teaching identity. However, there are still many questions about the process by which the social significance of the profession occurs in this context. Therefore, the present thesis sought to answer the following research question: What is the influence of the discipline of Supervised Internship for the Teaching in Sciences of a Biological Sciences Degree Course for the constitution and resignification of the teaching identity of the licenciandos? From this problematic, we seek in the theoretical foundation of Serge Moscovici's Theory of Social Representations and the epistemology of Ludwik Fleck to identify the representations of teaching shared by licenciandos and to understand how the concepts of style and collective of thought elucidate the process of genesis and transformation of the teaching identity. Thus, in order to reach these objectives, we performed the data collection with 12 students in the subject of Supervised Internship for Teaching in Sciences in a course of Degree in Biological Sciences of a Public University of the State of Paraná. We use word-free evocation and semi-structured interviews to compose the data that were analyzed with the Vergès framework and the Collective Subject Discourse (DSC) methodology. With these analyzes we verified the transformation of the social representations in socio-professional results of the change of social position of the subjects in the course of the research. We also contacted from the DSC the presence of two styles of thoughts, one based on social representations and another on the research field of teacher training and science teaching. These results enabled the understanding of the complexity of the identity phenomenon and pointed to the relevance of the proposal of analyzing the teacher identity from the dualistic perspective with the theoretical references of social representations and Fleckian epistemology in parallel, since the consensual and reified elements of teaching are interdependent in the identity phenomenon